2016
DOI: 10.3233/jad-160143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cerebrospinal Fluid and [11C]PIB PET Biomarkers for Alzheimer’s Disease with Updated Protocols

Abstract: Here, we improved controversial factors associated with the previous CSF study protocol and suggested a new cutoff value for the diagnosis of AD. Our results showed good diagnostic performance for differentiation of AD. Thus, we expect our findings could be a cornerstone in the establishment and clinical application of biomarkers for AD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…The magnitude of decrease in CSF Aβ42 and Aβ40 concentrations was similar, and consequently, Aβ42/Aβ40 was not significantly influenced by blood contamination. In line with our data, previous investigations have demonstrated that Aβ42/Aβ40 showed improved accuracy for AD diagnosis [2] and superior concordance with amyloid PET [32][33][34][35] in part by normalizing variability due to pre-analytical factors [11,25,36,37]. We did not observe any effects of blood contamination at levels that were not visible by the unaided eye (0.01% [500 E/μl] and 0.02% [1000 E/μl]) on CSF Aβ42.…”
Section: Discussionsupporting
confidence: 91%
“…The magnitude of decrease in CSF Aβ42 and Aβ40 concentrations was similar, and consequently, Aβ42/Aβ40 was not significantly influenced by blood contamination. In line with our data, previous investigations have demonstrated that Aβ42/Aβ40 showed improved accuracy for AD diagnosis [2] and superior concordance with amyloid PET [32][33][34][35] in part by normalizing variability due to pre-analytical factors [11,25,36,37]. We did not observe any effects of blood contamination at levels that were not visible by the unaided eye (0.01% [500 E/μl] and 0.02% [1000 E/μl]) on CSF Aβ42.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by previous literature, as outlined in a recent review [35]. For example, in a recent study, the tTau/Aβ(1–42) ratio increased concordance with PIB PET SUVR from 85.2% (κ statistic = 0.703, CI 0.51–0.89) with CSF Aβ(1–42) to 92.5% (κ statistic = 0.849, CI 0.71–0.99) [36]. This has also been shown for the pTau/Aβ(1–42) ratio, where in 103 mostly cognitively normal participants, CSF pTau/Aβ(1–42) showed greater sensitivity for detection of PIB+ compared with Aβ(1–42) alone [37].…”
Section: Discussionmentioning
confidence: 80%
“…Similar to our study, the authors also showed increased concordance to PET Aβ-amyloid when using ratios as compared to individual biomarkers. In addition, Leuzy et al, [39] and Wang et al, [40] also demonstrated highest concordance rates with PiB PET using the T-tau/Aβ42 ratio. In a large study assessing ratios for the diagnosis of AD, Janelidze et al, [19] showed that the Aβ42/Aβ40 and Aβ42/Aβ38 ratios were significantly better than Aβ42 alone at predicting PET Aβ-amyloid status using two different technologies (EUROIMMUN and MSD).…”
Section: Discussionmentioning
confidence: 91%